CORRELATION-BASED ANALYSIS AND LINEAR REGRESSION MODELING OF SYNCHRONIZED EEG AND ECG SIGNALS MEASUREMENT - Asst. Prof. Dr. Naufel Bahjat Mohammed (Journal Park Publishing, 2023)
This research aims to study the correlation between EEG and ECG signals measured at the same time. The correlation analysis of both signals will help to recognize the patient’s mental condition and its effect on heart activity.
Keywords: Correlation, EEG, ECG, Linear Regression, Raspberry Pi4.